2013
DOI: 10.3846/btp.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Filantropinė įmonės atsakomybė ir veiklos rezultatai: gamybos įmonės atvejis

Abstract: santrauka. Pastaruoju metu įmonės skatinamos tapti socialiai atsakingos ir investuoti į socialiai atsakingą veiklą. Socialinės atsakomybės samprata mokslinėje literatūroje yra itin kompleksiška, apimanti įmonės pilietiškumą, darnų vystymąsi, interesų grupių valdymą, aplinkos valdymą, verslo etiką ir įmonės socialinės veiklos rezultatus. Kita vertus, šiuolaikinė mokslinė literatūra verslo socialinės atsakomybės klausimais iš esmės pabrėžia socialiai atsakingos veiklos ir įmonės pelningumo sąryšį. Straipsnyje an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The concept of social responsibility in the scientific literature is extremely complex, involving corporate citizenship, sustainable development, stakeholder management, environmental management, business ethics, and the results of corporate social performance. On the other hand, the contemporary scientific literature on corporate social responsibility issues basically emphasizes the connection between socially responsible activity and company profitability [60]. Despite the arising debate, McAdam and Leonard [61] state that corporate social responsibility is characterized by multiplicity, encompassing such areas…”
Section: Introductionmentioning
confidence: 99%
“…The concept of social responsibility in the scientific literature is extremely complex, involving corporate citizenship, sustainable development, stakeholder management, environmental management, business ethics, and the results of corporate social performance. On the other hand, the contemporary scientific literature on corporate social responsibility issues basically emphasizes the connection between socially responsible activity and company profitability [60]. Despite the arising debate, McAdam and Leonard [61] state that corporate social responsibility is characterized by multiplicity, encompassing such areas…”
Section: Introductionmentioning
confidence: 99%
“…Matkevičienė [69] examined the peculiarities of social responsibility activities expression of Lithuanian alcohol producers, Šimanskienė and Paužuolienė [70] analyzed the organizational culture and corporate social responsibility connection: the study involved 55 companies that have proclaimed themselves as socially responsible. Virvilaitė and Daubaraitė [71] studied the expression of corporate social responsibility shaping the image of the private sector organization, Juščius and Jonikas [72] analyzed the integration of corporate social responsibility into the value formation chain, Navickas and Kontautienė [73] highlighted the shortages of businessmen's attention and competences in the implementation of social responsibility innovation, Korsakienė and Marcinkevičius [74] found that the cost of philanthropic responsibility does not affect the profit. Arlauskienė and Vanagienė [75] researched the representation of corporate social responsibility in companies' advertising campaigns.…”
Section: Trends Of Corporate Social Responsibility Studies In Lithuaniamentioning
confidence: 99%
“…Lietuvos mokslininkai (Leitonienė, Šapkauskienė 2012;Korsakienė, Marcinkevičius 2013;Laurinavičius, Reklaitis 2011;Išoraitė 2013) teigia, kad įmonių socialinės atsakomybės pagrindą sudaro darnaus vystymosi principų pritaikymas savo veikloje, t. y. įmonių pasaulėžiūra, politika ir praktika, kuri atvaizduoja tokią įmonių elgseną, kai jos į savo veiklos sritis savanoriškai įterpia aplinkosaugos ir socialinius aspektus, taip pat santykiuose su visais susijusiais visuomenės, verslo ir valdžios atstovais taiko pagarbos žmogui, visuomenei ir aplinkai vertybinius principus. Taip pat socialinė atsakomybė traktuojama kaip atsakas į ekonomikos globalizacijos keliamas visuomenės susvetimėjimo grėsmes arba kaip pareiga, kuri dera su organizacijos vertybių sistema, etiniu vadovų požiūriu, veiklos politika, aprėpia socialiai atsakingą, dorovingą įmonės valdymą, efektyvų išteklių taikymą, pažangias technologijas, aplinkosaugos reikalavimus, organizacijos darbuotojų, vartotojų ir visuomenės interesų paisymą, aukšto standarto taikymo kultūrą ir socialiai atsakingą investavimą.…”
Section: įVadasunclassified